«THE SERVANT OF GOD WISHED TO TURN THE DISSOLUTE DAY INTO THE DAY OF PRUDENCE, HOLINESS AND GOOD FOR THE SOUL» - Elena P. Telmenko (Вестник Северо-Кавказского федерального университета, 2022)
This article deals with practice on organization of «bonfire of vanities» in Florence in the late 15th century, at the same time special attention is paid to connection between Savonarola «pious» holidays аnd carnival culture.